Clinical research, national studies and grant applications: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Stafford, N
Abstract: Head and neck cancer clinical research is thriving. Infrastructure for clinical research is supported through the National Institute for Health Research Clinical Research Network with operates through 15 local clinical research networks for studies within the UK Clinical Research Network Portfolio. The National Clinical Research Institute is a partnership of UK cancer research funders that support high-quality cancer research, although the National Institute for Health Research also has funding streams that will fund cancer-related research. Their websites provide up-to-date information regarding ongoing research projects. Other specialty organisations such as the British Association of Head and Neck Oncologists play important subsidiary roles in supporting research.